2014
DOI: 10.2174/1874434601408010043
|View full text |Cite
|
Sign up to set email alerts
|

Stroke: Bowel Dysfunction in Patients Admitted for Rehabilitation§

Abstract: Aim : to assess the prevalence of diminished frequency of bowel movements, lumpy or hard stools, intestinal constipation, straining, incomplete evacuation, incontinence (bowel dysfunctions) in patients with brain injury resulting from cerebrovascular accident, either self-reported or reported by their caregivers; to describe the type and frequency of such dysfunctions; and the prevalence of laxative use both before and after stroke.Method : cross-sectional study with 98 hospitalized patients admitted for rehab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 16 publications
0
28
0
3
Order By: Relevance
“…Four studies (632 patients) [18,21–23] were conducted in the acute stages of a stroke, and 5 studies (753 patients) [17,19–21,24] were conducted in phases of rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (632 patients) [18,21–23] were conducted in the acute stages of a stroke, and 5 studies (753 patients) [17,19–21,24] were conducted in phases of rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, intestinal symptoms are very common in stroke survivors. The prevalence of functional constipation in this population ranges from 50% in the first month following a stroke to 30% after a mean of 36 weeks [4][5][6]. Moreover, this complication occurs independently of the side of the brain affected [7].…”
Section: Introductionmentioning
confidence: 94%
“…The causes of constipation include immobility, insufficient water intake, lowered consciousness, abnormal colon contractibility, and the side effects of medications. Among stroke survivors, this disorder has been explained by neurological impairment, dependence and a prolonged hospital stay as well as motor, cognitive and communicative impairments [3][4][5]. Moreover, studies have demonstrated that colon transit is significantly reduced in stroke survivors, which Mach attributes to the dysregulation of the central nervous system combined with abnormal passive movement of the visceral organs caused by limitations in body movements [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke juga menjadi penyebab kecacatan nomor satu yang menyebabkan >20% penderitanya mengalami ketergantungan perawatan dan lebih dari 30% menderita kecacatan permanen (Ghani, Mihardja, & Delima, 2016;Smith, English, & Johnson, 2012). Immobilisasi pada pasien stroke mengakibatkan perubahan tingkat kenyamanan dan perubahan fungsi sistem tubuh seperti ganguan pada sistem gastrointestinal yaitu konstipasi (Engler et al, 2014).…”
Section: Pendahuluanunclassified
“…Adanya cidera serebrovaskuler mengakibatkan gangguan fungsi neurologis pasien stroke mulai dari perubahan sistem kardiovaskuler, pernafasan, kemampuan mobilisasi, pencernaan maupun eliminasi. Gangguan sirkulasi di otak dapat menjadi suatu interupsi antara sistem saraf pusat dan sistem gastrointesinal yang berakibat konstipasi (brain-gut axis effect) (Engler et al, 2014). Perubahan brain-gut axis ini mempengaruhi sistem bowel yang dikontrol oleh sistem saraf enterik, sistem saraf otonom, sistem saraf volunter, hormon dan isi intestinal (Guyton & Hall, 2006;Sherwood, 2012).…”
Section: Tingkat Keparahan Strokeunclassified